Isolation and characterization of bio-active compounds from euphorbia inaequilatera and dicerocaryum senecioides - Ngobeni, Alister (University of Limpopo (Turfloop Campus), 2012)
This study was carried out to investigate antioxidant and antibacterial properties of 9 indigenous medicinal plants, viz., Euclea undulata (mogweregwere), Momordica balsamia (mogapu badimo), sefapa badimo, Senecio asperulus (makgonatšohle), Stiburus alopecuroides (mošalašuping), serolana, Euphorbia inaequilatera (kgama-maswana), mokgagapitsi and Clerodendrum glabrum (mohlokohloko) and to further isolate compounds that relate to these properties. Four extracting solvents with varying polarities viz. n-hexane, dichloromethane, acetone and methanol were used to extract the bioactive compounds from the ground powdered plant materials. The TLC plates, developed in three solvent systems viz., benzene, ethanol and ammonia (BEA, 18:10:0.2, v/v/v); ethyl acetate, methanol and water (EMW, 10:1.35:1, v/v/v) and chloroform, ethyl acetate and formic acid (CEF, 10:8:2, v/v/v), were visualised using DPPH, vanillin-sulphuric acid, visible light at 366 nm, UV light at 254 nm and bioautography for the presence of potential antioxidant and antibacterial compounds. The results of the screening process showed that only four plants possessed antioxidant compound(s) while six plants had antibacterial activity against Staphylococcus aureus. Euclea undulata “MKK” was observed to possess both antibacterial and antioxidant active compounds. Two antioxidant active compounds were isolated from two plants, viz., Euphorbia inaequilatera and Dicerocaryum senecioides. Solvent-solvent extraction, column chromatography and preparative TLC were used to further isolate and characterise target compounds. The antioxidant active compounds were found to separate well under EMW, an indication that the compounds are polar and intermediate-polar. The NMR spectra of the compound isolated from the D. senecioides revealed that the compound is a stilbenoid. For the first time, we report that the anti-inflammatory, antioxidant and antiproliferation properties of the D. senecioides reported by other studies performed in this laboratory could be due to this isolated stilbenoid compound. However, further studies are still necessary to confirm this assertion.
Thesis (M.Sc. (Biochemistry)) --University of Limpopo, 2013
Keywords: Antioxidants; Indigenous medical plants; 615.321; Antibacterial agents; Marine biodeversity